Media strategy in covering religious conflicts: a case study of Ahmadiyah conflict in West Java, Indonesia - Dulwahab, Encep; Abdullah, Aceng; Eni Maryani,; Muhtadi, Asep Saeful (Penerbit Universiti Kebangsaan Malaysia, 2021)
The Ahmadiyah conflict in Indonesia is often publicised by the Indonesian mass media at local and national level. The media plays an important role in covering conflict and there is a great interest among media and communication researchers to investigate media portrayals of these events. Most studies focused on the role of the media and journalists in the conflict. Very limited study however focused on media approach or analysing media strategies in covering the conflict. This research aims to explore strategies by two newspapers i.e: the Pikiran Rakyat (the biggest newspapers in West Java) and Republika (one the biggest newspapers in Indonesia) in reporting the Ahmadiyah religious conflict in Indonesia. Applying a qualitative approach, using a case study method, this research revealed that both media outlets applied four strategies in covering the Ahmadiyah conflict. These strategies are: (1) Building and maintaining good relations with news sources, which includes people involved in the conflict and witnesses; (2) Establishing a basecamp in which the journalists can focus on covering the conflict for a longer period; (3) Conducting interviews with news informants and making efforts to be accepted by the local people by mingling with the community and showing their neutrality stance; (4) Presenting and maintaining the accuracy of news. The result of this study is expected to contribute to the emerging literature on media and conflict, as well as understanding journalistic practice in covering various religious conflicts in Indonesia and beyond.